2017
DOI: 10.1007/s40092-017-0203-0
|View full text |Cite
|
Sign up to set email alerts
|

Two phase genetic algorithm for vehicle routing and scheduling problem with cross-docking and time windows considering customer satisfaction

Abstract: Cross-docking is a new warehousing policy in logistics which is widely used all over the world and attracts many researchers attention to study about in last decade. In the literature, economic aspects has been often studied, while one of the most significant factors for being successful in the competitive global market is improving quality of customer servicing and focusing on customer satisfaction. In this paper, we introduce a vehicle routing and scheduling problem with cross-docking and time windows in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…For large-size instances, developing a hybrid algorithm provides better results. e genetic algorithm is an intelligent heuristic technique for solving vehicle routing problems by reducing delivery costs significantly, and the following papers prove this: [25][26][27]. us, this paper chooses two well known and proven algorithms to solve the mixed delivery problem efficiently.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…For large-size instances, developing a hybrid algorithm provides better results. e genetic algorithm is an intelligent heuristic technique for solving vehicle routing problems by reducing delivery costs significantly, and the following papers prove this: [25][26][27]. us, this paper chooses two well known and proven algorithms to solve the mixed delivery problem efficiently.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…e genetic algorithm is a well-known and powerful algorithm to solve different vehicle routing problems, reducing delivery costs significantly by producing better solutions. e following papers are proof of this: [25][26][27]46]. And Branke et al [49] showed that the hybrid algorithm could better reduce logistics costs than simple heuristics by developing an evolutionary algorithm (EA), combining savings heuristic for transport channel selection and vehicle routing problem.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Ross [25], Mousavi [26], and Seyedhoseini [27] proposed cross-dock networks where the cross-dock location varied in response to decisions. Ali [28] proposed the MILP model presented for this problem to increase customer satisfaction by minimizing transportation costs and early/tardy deliveries by scheduling inbound and outbound vehicles. Dondo [29] studied an N-echelon vehicle-routing problem with cross-docking in supply chain management and dealt with the operational management of hybrid multi-echelon distribution networks.…”
Section: Literature Reviewmentioning
confidence: 99%